Exploring the relationship between job satisfaction (as measured by the JDI) and sales executive performance at a private South African Motor Retail Group - McNaughton, Peter (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
This study explores the relationship of job satisfaction as measured on the Job Descriptive Index with sales performance per individual, aimed at investigating the relationship between job satisfaction and a sales executive's performance. The Kelston Motor group was nominated as the organisation which the study would be conducted on. The approach to this study was to provide a sound academic base followed by a quantitative analysis. The Job Descriptive Index (JDI) questionnaire was used to determine the sales executives' current satisfaction levels and these where compared to the sales average gross profit incomes averaged out over a 6-month period. A sample of 34 sales executives employed by the Kelston Motor group were sent the JDI questionnaire. These individuals were selected based on the length of time they have worked for the organisation. Each sales executive was given a pseudonym to ensure anonymity. The various sales executives average monthly gross profit earnings over a 6-month period were linked to these pseudonyms. This information was then linked to each respondent's questionnaire before sending the questionnaire via email. The results of this study show that job satisfaction played a fairly insignificant role on sales executives performance. It was, however, found that job satisfaction had a direct effect on activities such as staff turnover and absenteeism which does have a direct impact on sales executives performance.
Keywords: Job satisfaction -- South Africa -- Case studies; Employee attitude surveys -- South Africa; Kelston Motor Group (South Africa) -- Employees -- Attitudes